APLIKASI SISTEM INFORMASI AKUNTANSI DALAM PENERIMAAN KAS (Cash Revenue) DAN PENGELUARAN KAS (Cash Expenditure) BERBASIS KOMPUTER PADA CV. SAKHINDO PRATAMA - Mondra, Mondra (Jurnal Ekobistek, 2013)
Abstract - The research have been conducted at CV. Sakhindo Pratama is about accounting system of cash revenue and cash expenditure based computer, with the purposes that CV. Sakhindo Pratama can using a better system divided with the running used system. CV. Sakhindo Pratama have used computer with the program of Microsoft excel for processing of cash revenue and cash expenditure while the archive still in manual, because of that designed a new accounting system which using Visual Basic Version 6.0 programmable language that can save data with the database that can over come the delay of sales reports and purchases on the cash revenue and cash expenditure with still used in the old accounting system. The method used are qualitative and design system method. From analysis which have been conducted so produced the new flows of system information with design input, process and output of cash revenue and cash expenditure at CV. Sakhindo Pratama. With the existence of this new system design and information flows that arranged and designed by the writer was hope able to over come the delay in reporting sales and purchase report in CV. Sakhindo Pratama specially in cash revenue and cash expenditure. Field Key : Cash Revenue, Cash Expenditure,accounting information system